2022
DOI: 10.3389/fpubh.2022.767591
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Renal Fibrosis in Diabetic Kidney Disease From 1985 to 2020

Abstract: BackgroundDiabetic renal fibrosis (DRF) is an irreversible renal pathological change in the end-stage of diabetic kidney disease (DKD), which plays a significant role in the development and deterioration of the disease. However, data for bibliometric analysis of renal fibrosis in DKD is currently missing. This study aimed to provide a comprehensive and visualized view of DRF research and lay the foundation for further studies.Materials and MethodsFirstly, the data was collected from the Web of Science Core Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…However, in the face of massive information in this topic, researchers need to dedicate a great deal of time to reading and understanding appropriate work in interrelated disciplines. Hence, it is imperative to classify substantial, classical, and evocative evidence to assist the scientific investigation (19). Although several literature reviews and metaanalyses are able to provide useful information and reliable evidence-based medical findings, these methods are often unable to make a summary from a holistic and integrated perspective for a specific field of research (20,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the face of massive information in this topic, researchers need to dedicate a great deal of time to reading and understanding appropriate work in interrelated disciplines. Hence, it is imperative to classify substantial, classical, and evocative evidence to assist the scientific investigation (19). Although several literature reviews and metaanalyses are able to provide useful information and reliable evidence-based medical findings, these methods are often unable to make a summary from a holistic and integrated perspective for a specific field of research (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Taking DM and metabolic bone disorders as examples, multiple investigators have studied the scientific outputs and publication trends of diabetes-related research across different countries via bibliometric approaches (26)(27)(28). DM-associated complications such as diabetic foot ulcers (29), diabetic nephropathy (19,30), and diabetic ophthalmopathy (31), etc. have also been studied with this approach.…”
Section: Introductionmentioning
confidence: 99%
“…The publications were obtained from the Core Collection database of Web of Science (WoSCC) because it is generally considered one of the most systematic, authoritative and comprehensive databases and has been widely used for scientometric analysis and visualization of scientific documents in a considerable number of studies ( 22 26 ). All searches were completed and downloaded on 1 day, March 20, 2022, to avoid the bias caused by daily database updates and verified by two authors independently.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Zhang et al analyzed diabetic kidney disease-induced renal fibrosis research through bibliometric analysis and revealed the top contributing countries and authors and the most popular journals in this field. Most importantly, they also demonstrated main research topics, including “microRNAs”, “bone morphogenetic protein”, “hypertrophy”, “glomerulosclerosis”, and “diabetic kidney disease”, and identified that “microRNAs” is a hot topic in recent works ( Zhang et al, 2022 ). Thus, bibliometric analysis can be performed to provide an in-depth evaluation of the development of the research concerning FGF-21, and this can guide us in future work.…”
Section: Introductionmentioning
confidence: 99%